Organic Fertilizers Vis-à-vis Growth Performance of Euphorbia fulgens - Florita O. Odivilas (European Scientific Journal, ESJ, 2016)
This study was conducted to find out the effect of fertilizers on the performance of two hybrids of Euphorbia as indicated by growth and flowering performance. The experimental design with controlled variables was used in the study. The use of organic fertilizers like the use of animal dungs or wastes was proven effective based on the different trials made. In terms of the effect of the fertilizers in the growth performance, there were significant differences on plant height, stem girth, number of leaves, and number of shoots during the 20th, 50th and 80th days of observations. The number of flowers was found to have significant differences in all stages. When measured during the 80th day of observation, significant differences were shown in the size of flowers. However, insignificant difference was shown in the diameter of flower bracts. As to the growth parameters, carabao manure yielded more leaves, and shoots and taller Euphorbia Orchid. It also produced bigger stem girths, wider and longer leaf sizes of Siam Ruby hybrid. As to flowering parameters, carabao manure influenced the growth of more number of flower clusters and bigger sizes of flowers of Euphorbia Orchid. On the other hand, chicken manure also influenced the growth of more number of flowers per cluster of Siam Ruby during the 50th day observation and carabao manure during the 20th day observation.